The Analysis of The Level Of Water Pollution in Lake Tambau Nagari Kampung Batu Dalam Danau Kembar District Solok Regency Through a Histopathological Study of Fish Kidneys - Keiko Kasy Billah Keiko Kasy Billah; Abdul Razak; Yuni Ahda; Yusni Atifah (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Water pollution is an indicator of deviations that occur in the properties of water from normal conditions. Lake Tambau, which is located in Jorong Air Tawa Utara, Nagari Kampung Batu Dalam, Danau Kembar District, Solok Regency, is one of the sources of fisheries used by the community to cultivate fish. The decline in water quality in Lake Tambau can be seen through physical observations such as the lack of water clarity, which indicates pollution in the lake water. Changes in environmental conditions that occur in Lake Tambau will be closely related to changes in the structure of kidney function in fish. Therefore research on kidney histopathology in fish is important to do in order to analyze changes in the histological structure of fish kidneys and analyze the level of water pollution that occurs in Lake Tambau. From the results of histopathological analysis of fish kidneys that have been obtained in Lake Tambau, it was found that there was hypertrophy, congestion, and necrosis. The results of a simple water analysis show that Lake Tambau water has a cloudy color, the temperature is above the normal threshold, has a pH of 9, there is sediment, and the color changes to dark when mixed with tea water which can be concluded that Lake Tambau water is heavily polluted. Key words water pollution,histopatology of fish kidneys